Study of Molecular Interactions among Esters, Toluene and Aniline using Ultrasonic Technique - P. Vasantharani1, R. Ezhil Pavai1*, S. Renuka1, L. Balu2 (Journal of Experimental Sciences, 2010)
<div style="border-bottom: windowtext 1pt solid; border-left: medium none; padding-bottom: 1pt; padding-left: 0in; padding-right: 0in; border-top: medium none; border-right: medium none; padding-top: 0in; mso-element: para-border-div; mso-border-bottom-alt: solid windowtext .5pt;"> Abstract The interactions of esters (ethyl acrylate and ethyl benzoate) with common binary of toluene + aniline were studied using ultrasonic velocity, density and viscosity measurements at 303, 308 and 313K. From the experimental data, the acoustical parameters such as adiabatic compressibility (Î²), free length (Lf), free volume (Vf), internal pressure (Ï€i), acoustic impedance (Z) and their excess values were estimated using standard relation. The results of these parameters are attributed to weak hydrogen bond between solute and solvent molecules. Â <div style="border-bottom: windowtext 1pt solid; border-left: medium none; padding-bottom: 1pt; padding-left: 0in; padding-right: 0in; border-top: medium none; border-right: medium none; padding-top: 0in; mso-element: para-border-div; mso-border-bottom-alt: solid windowtext .5pt;"> Keywords: Ultrasonic study; ternary mixtures; acoustical parameters; molecular interaction 1Department of Physics, Annamalai University, Annamalainagar â€“ 608 002, Tamil Nadu, India; 2Faculty of Engineering and Technology, Annamalai University, Annamalainagar â€“ 608 002, Tamil Nadu, India Please Cite This Article As: R. Ezhil Pavai, S. Renuka, L. Balu and P. Vasantharani. 2010. Study of Molecular Interactions among Esters, Toluene and Aniline using Ultrasonic Technique. J. Exp. Sci. 1(6):21-24